SMS-Aided teaching of reading in Malaysia: factors to consider - Mat Daud, Nuraihan; Husin, Zamnah (IIUM Press, 2012)
Students’ ability to perform successfully in the content area is often correlated with their ability to read and comprehend texts. However, the time spent on reading is often limited to a dedicated learning environment. To ensure that reading can be done regardless of time and space, mobile learning or MLearning through its mobile technologies such as mobile phones may offer another alternative to reading. As many students studying in a university own a mobile phone it can be used for teaching purposes. This research is on the use of mobile learning (Mlearning) particularly short message service (SMS) facility in developing second-language students’ reading skills. It aims to see whether mobile learning can complement traditional reading lesson. The study was conducted on language learners in an intensive English language programme at an institution of higher learning. SMSes were sent everyday within one semester to the selected students. The study shows that students found the approach interesting and helpful. Some mentioned that receiving the SMS daily had encouraged them to use English or read English materials more often. Others stated that the activity had enabled them to get access to English wherever they were and they liked receiving extra exposure to English through SMS in addition to classroom learning. Most of them appreciated the fact that they were chosen for the study and expressed hope that the Centre would adopt this approach. The study also highlighted possible problems when using this technology. Among them were telecommunication networks incompatibility and limitation on the number of characters per message.